Development of efficient strain of Ganoderma lucidum for biological stripping of cotton fabric dyed Reactive Blue 21 - Zainab Latif (Elsevier, 2021)
One of the most common dyeing problems of textile industries is uneven and faulty dyeing over the finished quality of fabrics due to different reasons. These problems are usually tackled through chemical degradation in which uneven and faulty dye is removed from the surface of fiber but fabric quality is compromised. Chemical process also reduces the strength of the fabric and durability of textile material by reduction in reactive dye ability. The fabric cannot be reused due to the reduced strength. To overcome above mentioned problem, biological method of stripping in which enzymes produced by different micro-organisms are used. This process has no harmful effect on the fabric and is safe for environment. In this research work reactive blue 21 dye with 0.5, 2 and 4% shade strengths was used to dye cotton fabric. The Ganoderma lucidum fungal strains were mutated by UV mutagen, and five were selected for further processing. These mutant strains were grown at temperature ranges (20 °C to 40 °C); pH(3–5); inoculum size(1–5 mL) and fermentation time (3–15 days) . The required nutrients media to produce the ligninolytic enzymes was added to the flask. The strain which gave the fast decolourization results was selected for further optimization. Optimization was done by observing the variables: incubation time 12 days, pH 4, temperature 30 °C, and inoculum size 3 mL by applying Response Surface Methodology (RSM) in Central Composite Design (CCD). During the process of fabric color stripping, the enzyme assay revealed that the respective mutant UV-60 strain produced active enzymes with their Vmax, Mnp (427U/mL), LiP (785U/mL), and Lac (75 U/mL) enzymes decolorized 89% of the dye which is 25% more than the parent strain and also the production of enzyme is Mnp (344U/mL), LiP (693U/mL), and Lac (59 U/mL) enzymes which is lower than mutant strain.